2019
DOI: 10.1016/j.epsl.2019.115798
|View full text |Cite
|
Sign up to set email alerts
|

Mantle plumes are oxidised

Abstract: From oxic atmosphere to metallic core, the Earth's components are broadly stratified with respect to oxygen fugacity. A simple picture of reducing oxygen fugacity with depth may be disrupted by the accumulation of oxidised crustal material in the deep lower mantle, entrained there as a result of subduction. While hotspot volcanoes are fed by regions of the mantle likely to have incorporated such recycled material, the oxygen fugacity of erupted hotspot basalts had long been considered comparable to slightly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 89 publications
(148 reference statements)
11
94
1
Order By: Relevance
“…Considering that Fe 3+ /Fe tot of 0.46 seems rather oxidized, we suggest that an oxygen fugacity of NNO+1.1 provides an upper bound for the phonotephrites. The calculated melt H 2 O contents are above those found in olivine-hosted melt inclusions from Fogo (up to 2.6 wt%; Moussallam et al, 2019), but appear plausible considering the differentiated nature of the phonotephrites compared to the mafic tephras investigated by these authors.…”
Section: Amphibole Thermobarometry and Hygrometrymentioning
confidence: 53%
See 2 more Smart Citations
“…Considering that Fe 3+ /Fe tot of 0.46 seems rather oxidized, we suggest that an oxygen fugacity of NNO+1.1 provides an upper bound for the phonotephrites. The calculated melt H 2 O contents are above those found in olivine-hosted melt inclusions from Fogo (up to 2.6 wt%; Moussallam et al, 2019), but appear plausible considering the differentiated nature of the phonotephrites compared to the mafic tephras investigated by these authors.…”
Section: Amphibole Thermobarometry and Hygrometrymentioning
confidence: 53%
“…Petrological studies of Fogo provided detailed data for the magma plumbing systems of the 1951, 1995, and 2014-2015 eruptions (Munhá et al, 1997;Hildner et al, 2011Hildner et al, , 2012Mata et al, 2017), thermobarometric data for earlier eruptions (Hildner et al, 2012), and analyses of some melt inclusions (Moussallam et al, 2019). These studies showed that the erupted magmas were stored before eruption within the uppermost mantle between 15 and 30 km depth, and stalled during ascent within the lower crust at 8-13 km depth.…”
Section: Geological Overview Of Fogomentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scenario might occur during graphite-saturated melting (e.g., Eguchi and Dasgupta, 2018b). However, the Fe 3+ /Fe 2+ ratios of basalts and melt inclusions from MORB and ocean islands indicate the mantle is not sufficiently reduced for graphite-present melting to occur ubiquitously (Bézos and Humler, 2005;Cottrell and Kelley, 2011;Shorttle et al, 2015;Berry et al, 2018;Moussallam et al, 2019).…”
Section: A Global Array Controlled By the Melting Process?mentioning
confidence: 99%
“…In a second session (in 2018), XANES spectra were collected for the 6 experimental glasses and the 11 MIs from FS tephra characterized in this study, along with 3 MIs from (1 MI from 2002/2003, 1 from 2013 and 1 MI from FS eruptions) following the methodology described in Moussallam et al, (2019). The X-rays were focused with Kirkpatrick-Baez mirrors down to 2 µm (horizontal) × 1.2 µm (vertical) beam size.…”
Section: Xanes Fe 3+ /ʃFe Investigationmentioning
confidence: 99%